Role of Camouflage in Management of Facial Trauma Deformities - Chin, Oliver Y.; Tollefson, Travis T. (Facial Plastic Surgery, 2017)
Facial fractures and soft tissue injuries around the eyes, nose, and mouth can be difficult to manage in the primary setting, but if untreated, the secondary correction of facial trauma is very challenging. Prevention of soft tissue contraction by restoring the skeletal framework is ideal. Staged, individualized camouflage techniques can be effective in improving outcomes.
Keywords: scar; fat graft; patient-specific implant; craniomaxillofacial; facial trauma; camouflage; posttrauma deformities